Parking Query in Vehicular Delay-Tolerant Networks with Privacy Protection Based on Secure Multiparty Computation. (2nd August 2015) - Huang, Haiping; Feng, Juan; Sha, Dan; Xu, Jia; Dai, Hua
Abstract : Within vehicular delay-tolerant network, conflict exists in the scenario of which two vehicles happen to choose the same parking space. To solve this problem, two protocols are proposed, respectively, which are called privacy protection protocol based on secure multiparty computation and routing protocol based on angle and density. The proposed methods prevent the leaking of privacy information of the vehicles involved during the parking space seeking process and improve the performance of the transmission ratio and reduce the transmission delay by unifying the directions of messages and choosing the vehicle of the highest distribution density as the next hop. The results of the simulation show the efficiency of our method.